Estimating the clinical effectiveness and value-based price range of erenumab for the prevention of migraine in patients with prior treatment failures: a US societal perspective. (3rd July 2018) - Lipton, Richard B.; Brennan, Alan; Palmer, Stephen; Hatswell, Anthony J.; Porter, Joshua K.; Sapra, Sandhya; Villa, Guillermo; Shah, Neel; Tepper, Stewart; Dodick, David
Abstract: Background: Frequent migraine with four or more headache days per month is a common, disabling neurovascular disease. From a US societal perspective, this analysis models the clinical efficacy and estimates the value-based price (VBP) for erenumab, a fully human monoclonal antibody that inhibits the calcitonin gene-related peptide receptor. Methods: A Markov health state transition model was developed to estimate the incremental costs, quality-adjusted life-years (QALYs), and value-based price range for erenumab in migraine prevention. The model comprises "on preventive treatment", "off preventive treatment", and "death" health states across a 10-year time horizon. The evaluation compared erenumab to no preventive treatment in episodic and chronic migraine patients that have failed at least one preventive therapy. Therapeutic benefits are based on estimated changes in monthly migraine days (MMD) from erenumab pivotal clinical trials and a network meta-analysis of migraine studies. Utilities were estimated using previously published mapping algorithms. A VBP analysis was performed to identify maximum erenumab annual prices at willingness-to-pay (WTP) thresholds of 100, 000–200, 000 per QALY. Estimates of VBP under different scenarios such as choice of different comparators, assumptions around inclusion of placebo effect, and exclusion of work productivity losses were also generated. Results: Erenumab resulted in incremental QALYs of 0.185 vs supportive care (SC) and estimated cost offsets due to reduced MMD of 8, 482 over 10 years, with an average duration of treatment of 2.01 years. The estimated VBP at WTP thresholds of 100, 000–200, 000 for erenumab compared to SC ranged from 14, 238–23, 998. VBP estimates including the placebo effect and excluding work productivity ranged from 7, 445–13, 809; increasing to 12, 151–18, 589 with onabotulinumtoxinA as a comparator in chronic migraine. Conclusion: Erenumab is predicted to reduce migraine-related direct and indirect costs, and increase QALYs compared to SC.